Effects of UV-B radiation on the infectivity of Magnaporthe oryzae and rice disease-resistant physiology in Yuanyang terraces. Issue 1 (7th November 2017) - Li, Xiang; He, Yongmei; Xie, Chunmei; Zu, Yanqun; Zhan, Fangdong; Mei, Xinyue; Xia, Yang; Li, Yuan
Abstract : The traditional rice variety "Baijiaolaojing" was planted in Yuanyang terraces a stable and sustainable rice field ecosystem under field conditions. Abstract : The traditional rice variety "Baijiaolaojing" was planted in Yuanyang terraces (1600 m altitude) under field conditions. The effects of enhanced UV-B radiation (0 kJ m −2, 2.5 kJ m −2, 5.0 kJ m −2 and 7.5 kJ m −2 ) on the rice– Magnaporthe oryzae system were studied with respect to the Magnaporthe oryzae infection, the disease-resistance physiology of the rice and the rice blast disease condition. The results showed that under enhanced UV-B radiation, the infectivity of Magnaporthe oryzae was decreased, which could significantly inhibit its growth and sporulation. The activities of rice leaf disease-resistance-related enzymes (phenylalanine ammonia-lyase, lipoxygenase, chitinase and β-1, 3-glucanase) were significantly increased under enhanced UV-B radiation. Following inoculation with Magnaporthe oryzae, levels of disease-resistance-related substances in the rice leaves were significantly increased. Among the results, it was found that leaves after UV-B radiation had a more significant resistance response. The level of UV-B irradiation showed a parabolic relationship with the rice blast index ( r 2 = 0.85, P < 0.01; in the control group, r 2 = 0.88, P < 0.01). The disease index decreased with increase in irradiation. The DI was at a minimum with enhanced UV-B irradiance of 4 kJ m −2 ; thereafter, it increased with increasing irradiation. The enhanced UV-B radiation had a direct impact on the growth of rice and Magnaporthe oryzae, and it indirectly changed the rice– Magnaporthe oryzae system. UV-B radiation could reduce the harmful impact of rice blast.